Day 3 Fri, August 26, 2016 2016
DOI: 10.2118/181805-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acid Fracturing Carbonate-Rich Shale: A Feasibility Investigation of Eagle Ford Formation

Abstract: Due to the extensive technically recoverable shale natural gas resources and an increase in production from shale plays over the last 10 years, it is essential to focus on stimulation techniques to enhance productivity in shale resources. One such stimulation technique is acid fracturing. Similar to hydraulic fracturing, acid fracturing injects acid into a formation at a pressure greater than the fracture pressure, creating fractures and etching the created fracture face. The high carbonate content of the Eagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…act as proppant to prop the fractures under closure pressure. The experiment of acidizing in shale by Cash et al 15 showed that acidizing with 28% HCL produces a high initial conductivity, which reduces sharply in the latter period, and treatment with 15% HCL produces a constantly high conductivity. It is thought that a higher content of carbonatite in shale results in a larger dissolution space, and high conductivity is likely to generate.…”
Section: Introductionmentioning
confidence: 99%
“…act as proppant to prop the fractures under closure pressure. The experiment of acidizing in shale by Cash et al 15 showed that acidizing with 28% HCL produces a high initial conductivity, which reduces sharply in the latter period, and treatment with 15% HCL produces a constantly high conductivity. It is thought that a higher content of carbonatite in shale results in a larger dissolution space, and high conductivity is likely to generate.…”
Section: Introductionmentioning
confidence: 99%
“…Acid fracturing for stimulating carbonate-rich shale, such as calcareous mudstone, has been examined as a method for improving conductivity and matrix permeability by etching the microfractures. , Experimental studies on different shale samples concluded that dilute acid concentrations that are optimized for specific materials are necessary to balance hydrocarbon recovery and unfavorable rock weakening by dissolving carbonate minerals from the rock matrix. These studies have provided an understanding of changing permeability, porosity, and constitutive properties that are utilized in continuum-scale models for simulating macroscopic fracture dynamics. , …”
Section: Chemical Reactions Of Hff With Minerals and Organic Matter I...mentioning
confidence: 88%
“…Thus, tracking the effect of changing one condition on the resulting conductivity will be a challenge. An extensive literature review was applied to gather published data on the API acid fracture conductivity experiments. ,,, It is worth mentioning that the data collected are consistent as they are obtained from the same laboratory using the same experimental procedure. Table illustrates the physical properties, meanings, and units of different features.…”
Section: Data Gathering and Handlingmentioning
confidence: 98%
“…A recent study has also shown that acid-fracture fluid type could alter the pattern of rock removal which has a significant effect on the conductivity, even more so than the volume of the dissolved rock . For example, conductivity is higher when the acid fracture treatment creates channels rather than rough surfaces, given that they could withstand closure stress. The leaking of acid from the fracture into the surrounding rock matrix can also result in more heterogeneous fracture surfaces that enhance conductivity if the rock’s mechanical properties are unharmed …”
Section: Introductionmentioning
confidence: 99%